Det globale gymet - Manligt og kvinnligt i simulakrats tidsålder - Thomas Johansson (The Royal Danish Library, 1997)
The article deals with the gender ideals cultivated within contemporary fitness and gym culture - in particular the paradoxical features of this culture. On the one hand, traditional gender ideals are maintained and strengthened; on the other hand, there is a development towards an androgynous ideal. The hard and "perfect" body is gradually becoming a dial for both men and women. Men as well as women are facinated by this sculptured and well-trained body. Thus the gym and fitness culture contributes to changes in and a more reflexive attitude towards gender and body ideals.